In vitro evaluation of the antimicrobial activity of the association of metabolites secreted from the symbiotics kefir and resveratrol, against microorganisms isolated from patients with hospital infections (Research, Society and Development, 2023)
Hospital-acquired infections are considered a public health problem, with an increasing impact on mortality and morbidity rates among patients and on the costs associated with hospital care. According to the World Health Organization (WHO), antimicrobial resistance is seen as one of the top ten global threats to public health, with its persistence mainly attributed to the inappropriate and excessive use of antimicrobials. In a review of the clinical development of antibiotics aimed at priority resistant pathogens, only six antibiotics were deemed promising by the WHO in 2019. Bacteria causing common infections are the group with the highest antibiotic resistance rates, underscoring the urgency for therapeutic alternatives. It is in this context that the search for new natural antimicrobial alternatives becomes advantageous. This study aims to evaluate, in vitro, the antimicrobial activity of the combination of metabolites secreted from the probiotics kefir and resveratrol against bacteria isolated from patients with hospital-acquired infections.